Zlín: Public Art and the City - Snedarova, Jana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
In this article, the topic of public art in an urban environment of the post-industrial city is viewed in the context of one place – Zlín. Contemporary artworks integrated into the city spaces show the city as a site, in the context of its Modernist architecture and urbanism. They reflect both the past and the present-day changes in society and the way how we see and experience the world. Public art in Zlín has become part of the transformation and regeneration of public spaces fostering the enhancement of the quality of lives of local urban residents. It is evident from the research that Zlín can be perceived as a place with great potential for new art projects and for the public’s participation and engagement.